Pembuatan Wadah Saus dari Material PLA dan Pati Kulit Singkong dengan Proses Injection Molding: Development of a Sauce Container Made from PLA and Cassava Peel Starch Using the Injection Molding Method - Salsabila, Tsabitah Nurma (Jurnal Rekayasa Mesin, 2026)
This study aims to develop an innovative eco-friendly packaging solution in the form of biodegradable sauce containers made from a composite of Polylactic Acid (PLA) and cassava peel starch using the injection molding process. The research is driven by the high volume of single-use plastic waste in Indonesia and the need to utilize agricultural waste as an alternative bioplastic material. The methodology employed is a quantitative experiment with processing temperature variations of 150°C, 160°C, and 170°C, while maintaining a fixed material ratio of 70% PLA and 30% cassava peel starch. The testing was conducted in two phases: using a manual injection molding system and an optimized system with pneumatic pressure. The results indicate that the pressing mechanism and temperature stability significantly influence the geometric and visual quality of the product. In the manual testing phase, 170°C provided the best geometry, although it remained unstable, while lower temperatures resulted in incomplete cavity filling (underfill) due to high viscosity. Conversely, in the pneumatic system, 150°C was found to be the optimal point, producing transparent sauce containers with the most precise dimensions and minimal defects. Increasing the temperature to 160°C and 170°C in the pneumatic system triggered an extreme drop in viscosity, leading to flash defects and thermal degradation, characterized by the products turning a dark brown color. This study concludes that the combination of pneumatic pressure and a temperature of 150°C is effective for producing biocomposite sauce containers of optimal quality.